The Status of Freshwater Fish Fauna in Bangladesh - Choudhury, Gawsia Wahidunnessa (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 19-44 Uploaded date: 31 May, 2011